Preliminary study of Autoimmune Polyglandular Syndrome (APS). Are they solely an endocrinological problem? - Malicka, Joanna Elżbieta; Kurowska, Maria; Kiszczak-Bochyńska, Ewa; Dudzińska, Marta; Malicka, Ewa; Tarach, Jerzy S. (Family Medicine & Primary Care Review, 2017)
Background . Autoimmune Polyglandular Syndrome (APS) forms a heterogeneous group of rare, genetically caused diseases, characterized by autoimmune activity against more than one endocrine organ, although non-endocrine organs can be also affected. APS was classified into four types. The two major types are APS-1 and APS-2. Objectives . The aim of this study was to evaluate the type, number and sequence of appearance of autoimmune diseases forming different types of APS in own material. Material and methods . The study involved 41 patients with APS (32 F; 9 M), aged 19–72 years (mean 45.2 ± 13.5). The authors analyzed medical histories and the results of additional tests. Results . In the entire group of patients, as well as in each type of APS, women predominated. The most frequently diagnosed type of APS, confirmed in 51.2% of patients, was APS-2. APS-3 accounted for 41.5% of APS. The most rarely observed, present in 7.3% of patients, was APS-1. The most common pathology was autoimmune thyroid disease, followed by Addison’s disease, and third – type 1 diabetes. The majority of patients (58.5%) were diagnosed with only two coexisting disorders, mainly Addison’s disease and thyroid disease. In 36.6% of patients, three diseases were recognized, while four autoimmune disorders were discovered in only two women (4.9%). The onsets of consecutive autoimmune diseases in individual patients from study group were spread in time and spanned up to 29 years maximum. Conclusions . If the patient exhibits autoimmune disorders, the suspicion of a further autoimmune disease should be present. A family history of autoimmune disease is also very helpful. A patient with APS needs life-long replacement therapy and observation by a family doctor, endocrinologist and other specialists to monitor the effectiveness of the treatment and detect new components of the syndrome.